A Legal Examination on Russia’s Threat on the Use of Nuclear Weapons during the Invasion of Ukraine based on the Applications under International Law - Christopher David Nagaria; Ariawan Gunadi (Universitas Ekasakti, 2024)
The purpose of this research hopes to provide viewers further awareness and contributions that promote the abolishment of nuclear weapons. The issue the researcher has found include what are the legal applications and laws regarding the threat and use of nuclear weapons. The research method used is doctrinal legal research which aims to examine and analyze the norms that govern the threat and use of nuclear weapons based on existing laws. The findings of this research include various regulations and treaty’s such as the Non-Proliferations Treaty which establishes the recognition of nuclear and non-nuclear weapon states, as well as the limits on the use of nuclear weapons, The Comprehensive Nuclear Test Ban Treaty is an agreement which aims to limit the development and testing of nuclear weapons, and most recently the Treaty on the Prohibition of Nuclear Weapons which prohibits nuclear weapons. However, the results have shown that the current laws are insufficiently enforceable and mainly agreed upon under good faith. President Putin’s threats to nuclear warfare and the transfer and stationing of nuclear weapons to Belarus are evidence for further developments and amendments to the treaties in addressing this problem.